Sense data's place in perceptual knowledge and phenomenology - Ong, May Yi Mei (2018)
Perceptual knowledge is an integral part of our acquisition of knowledge about the world. But how do our perceptual experiences contribute to knowledge? More importantly, what do we perceive? The problem of perception arises when cases of illusions and hallucinations cannot be accounted for by our ordinary conception of perception. Another aspect of perception that faces threats from non-veridical cases of perception is the phenomenology, or phenomenal character of perceptual experiences. A good theory of perception should hence be able to provide a unified account of perception across veridical and non-veridical cases and be able to address these two problems. In this paper, I seek to develop a refreshing take on the sense-datum theory to achieve the above aim, and defend the theory against threats posed by its direct realist contender, naïve realism. Conclusively, I will argue that my version of the sense-datum theory is better at accounting for perceptual knowledge and perceptual phenomenology than naïve realism, reinstating sense data’s place in both aspects of perception.